Policy options to overcome barriers to industrial energy efficiency in developing countries - Mallett, Alexandra (UNIDO ViennaAT, 2011)
Scrutinises the evidence supporting the view that there are barriers to energy efficient technologies considered profitable, that these barriers can be overcome, and that there are various mechanisms through which to address these barriers, but these actions have yet to be fully explored in developing countries.